1987
DOI: 10.1007/bf00324547
|View full text |Cite
|
Sign up to set email alerts
|

Effects of manganese oxide on monkeys as revealed by a combined neurochemical, histological and neurophysiological evaluation

Abstract: Four monkeys were exposed to a total of 8 g each of manganese as oxide by repetitive subcutaneous injections during 5 months, after which they were left for 1 week to 6 months before they were sacrificed. All animals developed hyperactive behaviour after about 2 months. About 5 months after the start of the exposure the animals became hypoactive with an unsteady gait, and subsequently an action tremor appeared in some of the animals. The animals lost power in both upper and lower limbs and the movements of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(73 citation statements)
references
References 27 publications
3
69
1
Order By: Relevance
“…In particular, the effect of manganese on motor function has been reliably reproduced in different animals and experimental paradigms; this effect is apparent across a wide range of doses, different routes of administration and chemical species of manganese (Calabresi et al, 2001;Dodd et al, 2005;Mohammad and Faris, 2006;Nam and Kim, 2008;Newland and Weiss, 1992;Normandin et al, 2004). Manganese treatment typically results in decreased motor activity or disturbances in motor coordination, although a manganese-induced hyperactivity has also been reported (Calabresi et al, 2001;Eriksson et al, 1987). The effects are usually reversible, dose-dependent and often remain long after the end of manganese administration.…”
Section: Manganese-induced Motor Dysfunctionmentioning
confidence: 97%
See 1 more Smart Citation
“…In particular, the effect of manganese on motor function has been reliably reproduced in different animals and experimental paradigms; this effect is apparent across a wide range of doses, different routes of administration and chemical species of manganese (Calabresi et al, 2001;Dodd et al, 2005;Mohammad and Faris, 2006;Nam and Kim, 2008;Newland and Weiss, 1992;Normandin et al, 2004). Manganese treatment typically results in decreased motor activity or disturbances in motor coordination, although a manganese-induced hyperactivity has also been reported (Calabresi et al, 2001;Eriksson et al, 1987). The effects are usually reversible, dose-dependent and often remain long after the end of manganese administration.…”
Section: Manganese-induced Motor Dysfunctionmentioning
confidence: 97%
“…Although the mechanisms underlying manganese neurotoxicity remain unclear, experimental evidence exists that manganese may affect dopaminergic and cholinergic neuromodulatory systems, which may lead to various cognitive and neurological disorders including motor dysfunction (Calabresi et al, 2001;Eriksson et al, 1987;Nam and Kim, 2008;Newland and Weiss, 1992;Olanow et al, 1996). Taking this into account, a successful application of MEMRI technique for longitudinal studies, particularly involving behaving animals, critically depends on the manganese administration regimen that does not or minimally compromise homeostatic capacity, while achieving MRI-detectable cumulative concentration of Mn 2+ in the brain.…”
Section: Manganese-induced Motor Dysfunctionmentioning
confidence: 99%
“…Due to the limited number of non-human primate studies of manganese neurotoxicity and the fact that results are mostly reported for individual animals, attempts to draw general observations from this dataset are necessarily tentative. The most consistent outcomes produced by manganese exposure are a decrease in striatal dopamine and a deleterious effect on globus pallidus integrity, variously characterized as damaged globus pallidus (Mella 1924), loss of pallidal neurons (Eriksson et al 1987b;Pentschew et al 1963), gliosis (Shinotoh et al 1995), proliferation of Alzhemimer Type II astrocytes (Pentschew et al 1963), and decreased globus pallidus dopamine content (Bird et al 1984).…”
Section: Non-human Primatesmentioning
confidence: 99%
“…The basal ganglia, and the dopaminergic neurons in particular, are most vulnerable to manganese (Eriksson et al, 1992, Stanwood et al, 2009, Sriram et al, 2010. As a result, motor extrapyramidal symptoms, resembling those of Parkinson's disease patients, are a common manifestation in humans (Huang et al, 1998, Tuschl et al, 2013 as well as in experimental animals (Eriksson et al, 1987, Olanow et al, 1996. Consequently, Mn 2+ doses used in MEMRI studies must be carefully evaluated, M A N U S C R I P T…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%